THEMATIC ANALYSIS OF SHARIA STOCK PORTFOLIO DIVERSIFICATION AND FINANCIAL RATIOS: A CONCEPTUAL STUDY BASED ON THE INDONESIAN SHARIA STOCK INDEX (ISSI) - Samsul Huda; Mohammad Anis Sumadi; Ashlihah; Binti Nur Asiyah; Muhammad Aswad (BEMJ: Business, Entrepreneurship, and Management Journal, 2025)
Indonesia’s sharia capital market, represented by the Indonesian Sharia Stock Index (ISSI), has shown rapid growth; however, sharia stock portfolio diversification practices and the use of financial ratios for profit optimization have not yet been applied systematically by investors. This study aims to thematically analyze various sharia stock portfolio diversification strategies and to explain the role of financial ratios in shaping an optimal portfolio based on issuers included in the ISSI. The method employed is a qualitative approach with a conceptual study design, using content analysis and thematic coding of secondary data sources, including journal articles, Islamic investment management books, Financial Services Authority (OJK) regulations, DSN MUI fatwas relevant to the sharia capital market, and official reports and documents related to the ISSI. The analysis identifies several main themes: diversification strategies based on sector and market capitalization, cross-instrument diversification within sharia assets, and strengthened risk management through stock selection grounded in profitability, leverage, liquidity, and valuation ratios. These findings indicate that integrating portfolio diversification strategies with the appropriate use of financial ratios has the potential to enhance returns on sharia stock portfolios while keeping risk within acceptable limits, thereby offering a conceptual contribution to the development of ISSI based sharia investment strategies.